Comprehensive mini-review: therapeutic potential of cannabigerol – focus on the cardiovascular system - Krzyżewska, Anna; Kloza, Monika; Kozłowska, Hanna (Frontiers in Pharmacology, 2025)
BackgroundsCannabigerol (CBG) is a non-psychoactive phytocannabinoid with a broad spectrum of biological effects. However, there is still too little research on its safety especially its effects on the cardiovascular system. Due to its agonist effects on alpha-2-adrenergic receptors (α2AR), it is speculated that it may have applications in the pharmacotherapy of metabolic syndrome, particularly hypertension. Thus, the aim of our review was to analyse the therapeutic potential of CBG in cardiovascular diseases.MethodsThe review was based on searches of the PubMed and Web of Science databases. Keywords were used to identify literature containing therapeutic and mechanistic information on CBG and its potential effects on the cardiovascular system.ResultsA review of the literature shows that CBG exhibits hypotensive effects in mice probably through α2AR agonism. Other numerous in vitro and in vivo studies show that CBG has anti-inflammatory, antioxidant effects and also regulates cell apoptosis. Cannabigerol improved tissue sensitivity to insulin, and also showed efficacy in inhibiting platelet aggregation. However, there are reports of adverse effects of high doses of CBG on liver architecture and function, which calls into question its usefulness and safety profile.ConclusionAbove mentioned beneficial properties of CBG suggest that it may be useful in treating hypertension and metabolic syndrome. However, there is still a lack of studies on the chronic administration of CBG and its effects on cardiovascular parameters in hypertension condition, which may be necessary to determine its safety and the need for future studies on other indications.